Kidney transplant-related knowledge and influencing factors in Chinese kidney transplant candidates and recipients: A cross-sectional study - Ma, Hangxia; Hu, Maosen; Wan, Jingjing (Frontiers in Public Health, 2023)
Objective To investigate the kidney transplantation knowledge of kidney transplant (KT) candidates and recipients, and to explore the related influencing factors. Methods From March to July 2022, a total of 170 KT candidates and 270 KT recipients were investigated in two tertiary and Grade A hospitals in Hunan Province, China, using demographic questionnaires and the Kidney Transplant Understanding Tool (K-TUT). Multiple linear regression was used to explore the influencing factors of related knowledge of kidney transplantation. Results The scores of kidney transplantation knowledge of the two groups were 50.67 (Ranged: 0–63) and 52.79 (Ranged: 0–62), indicating a middle level of knowledge. Education level and whether they have received health education were significantly associated with the knowledge level of kidney transplantation in both KT candidates and recipients. In addition, age and fertility status were only significantly associated with the knowledge level of kidney transplantation in KT recipients. Conclusion Our finding shows that the knowledge level of KT candidates and recipients is not optimistic, which suggests that healthcare providers should pay more attention to the health education of this population. In addition, future health education interventions should consider the education level, age, and fertility status factors affecting kidney transplantation knowledge in KT candidates and recipients.